A perspective on the controlled synthesis of iron-based nanoalloys for the oxygen reduction reaction. Issue 64 (26th July 2022) - Huang, Xiaoxiao; Wang, Chunxia; Hou, Yanglong
Abstract : In this feature, our recent progress on controllable Fe-based nanoalloy structures (iron–platinum (Fe–Pt), iron carbide (Fe–C), and iron nitride (Fe–N)) and their applications as oxygen reduction reaction (ORR) electro-catalysts have been illustrated. Abstract : The worsening ecological environment is calling for clean energy alternatives, among which hydrogen fuel cells have been one of the hot topics. The commercialized Pt/C catalyst for the oxygen reduction reaction (ORR) in the cathode of fuel cells is suffering from its high cost, serious scarcity and so on. Hence, the exploration on alternative ORR catalysts has attracted much attention. Iron(Fe)-based nanoalloys have shown advantages of low cost, high abundance, and pleasant ORR activity. In this feature, we have summarized Fe-based nanoalloy structures and our recent progress on controllable synthesis as well as their ORR performance, including iron–platinum (Fe–Pt), iron carbide (Fe–C), and iron nitride (Fe–N). Finally, the perspective on this type of ORR electrocatalyst is also discussed.